PENGARUH PEMANFAATAN INTERNET TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 9 PEKANBARU - Olivia Chintya Rhany; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract : This research is motivated by the use of the internet and students' learning motivation at SMA Negeri 9 Pekanbaru. The formulation of the problem in this study is whether there is an effect of using the internet on students' learning motivation at SMA Negeri 9 Pekanbaru. The purpose of this study was to determine how the influence of internet use on student motivation at SMA Negeri 9 Pekanbaru. The benefits of this research are theoretical benefits, namely that this research is expected to contribute to the field of education, especially those related to writing scientific papers. And the practical benefit is as a reference material in carrying out further research that is relevant to this research. The population in this study were students of SMA Negeri 9 Pekanbaru, amounting to 350 students. The sample in this study were students of SMA Negeri 9 Pekanbaru, totaling 70 respondents who were determined by random sampling technique. The data collection instruments are questionnaires, and documentation. Data processing with quantitative descriptive analysis using a simple linear regression formula with the help of the SPSS version 26.0 application by stating the hypothesis: there is an influence between the use of the internet on student motivation at SMA Negeri 9 Pekanbaru. Based on the results of research on the effect of internet use on students' learning motivation at SMA Negeri 9 Pekanbaru, there is a significant influence between the influence of internet use on students' learning motivation at SMA Negeri 9 Pekanbaru by 22.4%Key Words: Effect, Internet Utilization, Learning Motivation